2008
DOI: 10.1038/ijo.2008.174
|View full text |Cite
|
Sign up to set email alerts
|

The FTO gene and measured food intake in children

Abstract: Objective: Polymorphisms in the obesity-associated gene, FTO, have been linked with sensitivity to satiety in children, indicating FTO may be influencing one of the regulatory drivers underlying food intake. In this study, we tested the hypothesis that food intake in a standard eating behaviour paradigm in which palatable food is offered under conditions of satiety would be associated with FTO genotype status, after controlling for differences in body mass index (BMI). Methods: Participants were 131 children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
244
2
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(267 citation statements)
references
References 21 publications
13
244
2
8
Order By: Relevance
“…[15][16][17] However, in this study we found an interaction between rs9939609 genotype and the dietary fat and CHO content in DREE. The difference in DREE between LF and HF diet in TT subjects of 75 kcal/24 h may seem small considering baseline values of REE at 1800-1900 kcal/24 h. It is however a difference in DREE of more than 50%.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…[15][16][17] However, in this study we found an interaction between rs9939609 genotype and the dietary fat and CHO content in DREE. The difference in DREE between LF and HF diet in TT subjects of 75 kcal/24 h may seem small considering baseline values of REE at 1800-1900 kcal/24 h. It is however a difference in DREE of more than 50%.…”
Section: Discussioncontrasting
confidence: 75%
“…Intake of all macronutrients tended to be greater in A-allele carriers but especially so for fat intake. In addition, the few studies that examined the relationship between appetite 14 and dietary intakes 16,31 with FTO, were performed in children or adolescents. In this context, an understanding of the interactions between macronutrient intake or dietary components and the genotype is important to provide a basis for determining the role of dietary intake and habits in the prevalence and pathogenesis of important conditions such as type 2 diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FTO gene is highly expressed in hypothalamus, a region involved in appetite regulation, and the A-allele has been associated with increased energy intake, especially fat intake, [1][2][3] and altered appetite 4 in children. There is also evidence in adults implicating that the risk allele carriers consume more energy.…”
Section: Introductionmentioning
confidence: 99%